2020
DOI: 10.3390/biom11010016
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxicity of RNase-Derived Peptides

Abstract: Bacterial ribonuclease binase exhibits a cytotoxic effect on tumor cells possessing certain oncogenes. The aim of this study was to identify the structural parts of the binase molecule that exert cytotoxicity. Out of five designed peptides, the peptides representing the binase regions 21–50 and 74–94 have the highest cytotoxic potential toward human cervical HeLa and breast BT-20 and MCF-7 cancer cells. The peptides B21–50 and B74–94 were not able to enter human lung adenocarcinoma A549 cells, unlike BT-20 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…We assume that this is due to the ongoing processes of aggregation (ESI, Table S3). Due to the fact that the binase IC50 for a number of tumor cell lines is in the range 2.44×10 -6 to 4.1×10 -5 M, [8][9][10][11] a decrease in enzymatic activity at higher concentrations of the 5 and 6 complexes with binase may reduce the cytotoxic effects of the drug in relation to healthy cells. Thus the binase complexes, within the limits of their effective concentrations, can potentially prolong the action of the drug and lead to a longer lasting therapeutic effect.…”
Section: It Was Necessary To Determine the Complexes' Abilities To Pe...mentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that this is due to the ongoing processes of aggregation (ESI, Table S3). Due to the fact that the binase IC50 for a number of tumor cell lines is in the range 2.44×10 -6 to 4.1×10 -5 M, [8][9][10][11] a decrease in enzymatic activity at higher concentrations of the 5 and 6 complexes with binase may reduce the cytotoxic effects of the drug in relation to healthy cells. Thus the binase complexes, within the limits of their effective concentrations, can potentially prolong the action of the drug and lead to a longer lasting therapeutic effect.…”
Section: It Was Necessary To Determine the Complexes' Abilities To Pe...mentioning
confidence: 99%
“…8 One such RNase, Bacillus pumilus RNase (binase), inhibits the proliferation of human leukemic Kasumi-1 cells, lung adenocarcinoma cells, ovarian and breast cancer cells. 9 Previously it was shown that the binase stops the processes that are necessary for the survival of cancer cells, but does not reduce the viability of non-malignant cells. 10 The main advantage of using cytotoxic RNases is the structural organization of enzymes, which determines their penetration and interaction with cancer cell components, 11 however, the protein nature of ribonucleases leads to a decrease in the stability and duration of the protein preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The cloning of barstar and encoding of both barstar and barnase on a single plasmid enabled the production of active barnase in Escherichia coli [13]. From that time the barnase and its molecular twin Binase were used in numerous applications including folding studies [14,15], enzymatic activity investigation [16], protein-protein interactions investigation [17,18], positive selection of cloned inserts [19,20], providing male and female sterility in plants [21,22], crop defense system construction [23], specific cell depletion [24], virus elimination [25][26][27], and cancer cell killing [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Small molecule anti‐cancer drugs are the most commonly used chemotherapeutics, which exhibit promising anti‐cancer effects [8] . However, traditional chemotherapy of small molecule anti‐cancer drugs are suffered from severe side effects, [9] extensive drug resistance [10] and long treatment cycle, [11] which limit the clinical applications.…”
Section: Introductionmentioning
confidence: 99%